Comparison on the Developmental Trends Between Chinese Students Studying Abroad and Foreign Students Studying in China - Liu, Xuezhi (Journal of International Students, 2014)
China has been undergoing a new period of political stability, cultural prosperity, and social harmony since its reform and opening-up in the late 1970s. At the same time, the number of Chinese students studying abroad (CSSA) and foreign students studying in China (FSSC) has grown rapidly and steadily in the past three decades. With China’s participation in globalization, CSSA and FSSC are a significant part of China’s potential international human capital and, as such, CSSA and FSSC are in great need. Data of CSSA and FSSC in the past 34 years are collected and examined in this article, and the historical trends are depicted and compared. Relationships between the developments of CSSA and FSSC and the development of China’s economy can be validated and compared by regression analysis. The number of CSSA and FSSC in the next 10 years can be predicted by predicting China’s GDP in the same period.